Performance Management and Reward Systems in PT XYZ - Rahardjo, Kukuh M; Wibisono, Dermawan; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
This paper describes the performance management and reward systems as it has been, and should have been implemented in PT XYZ. The need for updating and implementing the updated PT XYZ’s performance management and reward systems are because there have been such business issues as higher failure rate in test bay and lower employee productivity if compared with the specified targets in the financial year of 2010-2011. Based on the following facts and theory: (1) ICMA International’s survey in 2010 of PT XYZ’s employees; (2) The expectancy theory model which describes that employee’s satisfaction and motivation are as functions of his or her last effort to performance expectancies, performance to reward expectancies and perceived attractiveness of rewards; and (3) intense communication between the president director and the president of union of PT XYZ of bonus scheme and salary increment, the author believes that the root causes of increase in failure rate in test bay and lower productivity are that the major employees of PT XYZ had less motivation and target commitments. These were due to their dissatisfaction with the implemented performance management and reward systems in PT XYZ. PT XYZ has decided to approach both short and long-term business solutions in handling the business issues. The short-term business solutions are more likely to be fire-fighting activities. They are developed and implemented for smoothening (daily) operational activities while the long-term solutions are developed to be in-line with PT XYZ’s long-term (strategic) plans or intents. Keywords: Performance management, failure in test bay, productivity.